Diagnosis and outcome of pregnancies with prenatally diagnosed fetal dextrocardia. (28th July 2014) - Oztunc, Funda; Madazli, Riza; Yuksel, Mehmet Aytac; Gökalp, Selman; Oncul, Mahmut
Abstract: Objective : To evaluate the incidence, associated cardiac and extracardiac malformations and clinical outcome of fetuses with dextrocardia. Method : A retrospective review of 3556 fetal echocardiograms between 2000 and 2011 revealed 39 cases of dextrocardia. Dextrocardia was defined as right-sided positioning of the fetal heart. Prenatal and postnatal records of the fetuses were reviewed. Results : The incidence was 1.1%. Of the 39 fetuses, 22 were primary dextrocardia and 17 were dextroposition. Diaphragmatic hernia was the most common cause of dextroposition with the incidence of 76%. Of the fetuses with dextroposition 35.5% had a cardiac anomaly. The survival rate of dextroposition was 31.2% and none of the survivors had an associated cardiac anomaly. Primary fetal dextrocardia was most common with situs solitus (45.4%), followed by situs ambiguous (36.3%) and then situs inversus totalis (18.1%). Structural cardiac malformations were found in 100%, 80% and 25% of fetuses with situs ambiguous, solitus and inversus, respectively. Of the dextroposition, 47.6% terminated pregnancy, 14.2% resulted in intrauterine death, 9.5% died after birth, and 28.5% survived. Conclusion : A wide spectrum of complex cardiac malformations are associated with fetal dextrocardia. Fetal echocardiography enables detection of complex cardiac anomalies so that parents can be appropriately counselled.